Child physical violence and the dental surgeon’s professional duty: A literature review - Sartori, Pamela; Struckel , Bárbara Brusco; Naufel , Fabiana Scarparo; Souza , Maria Daniela Basso de (Seven Editora, 2023)
This paper aimed to perform a non-systematic review of the literature on physical violence against children, addressing the following factors: indicators of maltreatment and legal aspects, as well as elucidating the importance of the dental surgeon in the diagnosis and the ideal conduct to be taken by him. Thus, through the analysis and discussion of the theoretical basis presented, we seek to establish the current Brazilian panorama on child physical violence. The study is divided into seven exposition topics: the abstract, the introduction, the objectives, the methodology, the literature review, the discussion, and the final conclusion, thus composing the desired content. The following journals were used for the formulation and preparation of the study: Latin American and Caribbean Literature on Health Sciences (LILACS), Brazilian Bibliography of Dentistry (BBO), Scientific Eletronic Library Online (SCIELO), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Portal CAPES. Articles from the last 18 years were used, searching for the following keywords: "abuse", "violence", "child abuse", "orofacial injuries" and "dentistry". Despite the scarcity of underreporting of this violence, it was found that the orofacial region is often the site of multiple injuries from physical violence, making clear the importance of the dental surgeon in identifying and reporting this violence. DOI:https://doi.org/10.56238/colleinternhealthscienv1-028